La cerámica del Período Intermedio Temprano en el valle de Asia, costa centro sur del Perú - Angeles Falcón, Rommel (2023)
The ceramic sequence for the Early Intermediate Period in the Central-South coast is poorly known. The excavations undertaken at the archaeological site of Huaca Malena, in the Asia-Coayllo Valley, as well as the survey of the lower- and mid-valley posit the presence of a ceramic style that may have been shared with the neighbouring valleys of Mala and Cañete. This paper presents the first stylistic sequence for the Asia-Coayllo Valley, which appeared at the beginning of the Early Intermediate Period, spread over the Unchor sector in the middle valley, and was succeeded by a tri-colour style that has been identified at Huaca Malena (in the lower Asia-Coayllo valley).